Stress Reaction Symptoms Due to Human Body Dissection among First Year Undergraduate Medical Students - Khattri, Jai Bahadur; Godar, Srijana Thapa (Journal of College of Medical Sciences-Nepal, 2025)
Background There is a concern regarding the psychological impact of human body dissection among undergraduate medical students. The objective of this study was to assess the prevalence of stress reaction symptoms due to human body dissection among undergraduate medical students and to compare the mean traumatic stress reaction score between different variables of the socio-demographic and clinical profiles. Methods This cross-sectional study is conducted among 73 first year medical undergraduate students of Manipal College of Medical Sciences, Pokhara, Nepal. A predesigned proforma was used to collect the sociodemographic and clinical variables of the participants. The Impact Events Scale-Revised (IES-R) questionnaire was administered after one week of the exposure of the students to human body dissection. The respondents scoring 33 and above in the Impact Events Scale-Revised were considered positive for stress reaction symptoms. Results The prevalence of stress reaction symptoms was 1.37%. The mean traumatic stress score was high among males, Nepali citizens, urban residents, and non-vegetarian’s respondents, if the respondent’s parents were from a medical background and who had past exposure to a dead body in reality as compared to other variables, but it was not statistically significant. Conclusions There was a low prevalence of stress reaction symptoms among the undergraduate students. The gender, nationality of the respondents, occupation of parents, place of origin, dietary habits, and past history of exposure to dead bodies in reality do not statistically affect the mean traumatic stress score. This study will be beneficial for a small percentage of students who needs psychiatrist support to adapt to the experience of dissection.